Socio-Economic Aspects of Tourism in the Modern Society - Premović, Jelena; Arsić, Ljiljana (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The specificity of the tourist market and the connection of modern tourist products with numerous economic and non-economic activities cause the multiplicity of socio-economic effects of tourism. The development of tourism creates opportunities for a number of other activities, which means that tourism is a significant factor in boosting the overall economic development. Tourism plays a particularly important role in the overall socio-economic development of underdeveloped countries and regions. Tourism can contribute to positive socio-economic development, but at the same time, inadequate and uncontrolled management of a tourist destination can have negative socio-cultural, but also economic consequences. The paper investigates the basic economic and socio-cultural aspects and impacts of tourism. The authors pay special attention to the analysis of the multiplying effects of tourism on the development of a particular destination. Starting from the history of travel and tourism as an activity, key motives and socio-economic effects, the 2008 World Economic Crisis, its origin, causes and consequences of its impact on the entire world economy, especially tourism, the authors analyzed the current economic indicators of tourism activity in the world economy and projections of expected trends. In this paper, the focus of the analysis is on the tourist travel and economic and socio-cultural impact of tourism on the tourist destination, the individual, and the society as a whole.